Electrochemical formation of Sn films on copper by overpotential and underpotential electrodeposition in deep eutectic solvents - Azpeitia, Leticia Anahi (2023)
The electrodeposition process of tin films on copper electrodes in ethaline and reline deep eutectic solvents (DES) was studied in the 303 – 353 K range. Voltammetric data indicate the presence of underpotential and overpotential electrodeposition processes. While the former occurs under surface-reaction control, the latter proceeds under mass transport control. Electrochemical impedance spectroscopy shows two capacitive contributions during the underpotential process and a single capacitive contribution at high frequencies and a Warburg contribution at low frequencies, when the electrodeposition process takes place in the overpotential region. Tin deposits obtained in ethaline exhibit blunt particles with ordered structures whereas in reline facetted particles with no preferential order are observed as electrodeposition time is increased. The electrocrystallization mechanism under overpotential conditions in ethaline and reline corresponds to an instantaneous nucleation and a 3D growth process. For underpotential conditions in ethaline, an instantaneous nucleation and 2D growth coupled to an adsorption process occurs. XRD spectra shows the formation of Cu3Sn and Cu6Sn5 intermetallics due to the diffusion of Sn atoms into the Cu lattice during the electrodeposition process. From rotating disk electrode measurements, the diffusion coefficient of Sn(II) ions in both DES at different temperatures, and the diffusion activation energy, were determined.